Studi Eksperimen: Edukasi Sleep Hygiene dan Terapi Kognitif Perilaku terhadap Kecanduan Gawai Remaja di Kota Jambi - Nurlinawati Nurlinawati; Riska Amalya Nasution; Meinarisa Meinarisa; Yuliana Yuliana (Universitas Batanghari Jambi, 2023)
Device users in Indonesia are dominated by teenagers. Excessive use of gadgets can lead to gadget addiction and the risk of experiencing mental health problems. The purpose of this study was to determine the effect of sleep hygiene education and cognitive behavioral therapy on adolescent device addiction in Jambi City. The research design used was